2006
DOI: 10.1097/01.ss.0000187358.54858.33
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Sorption in Soils 25 Years After Amendment With Sewage Sludge

Abstract: Long-term changes in the solubility and bioavailability of heavy metals in soils, accumulated as the result of waste application, cannot be predicted without knowledge of the nature of metal retention in these soils. To test the theory that Fe-and Al-rich mineral phases in sewage sludge-amended soils can act as long-term sinks for heavy metals, soils were sampled from two field sites, each with a similar history of multiyear application of either high-Fe, high-Al, or high-Ca sludge (¨25 years earlier) but with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
2
5
0
1
Order By: Relevance
“…Apparently, the TZ soil is heavily contaminated with Cd and Cu whereas this is the case with respect to Cd and Zn for the FY soil. The ratio between the reactive Cd concentrations as determined by soil extraction with 0.43 M HNO 3 and the aqua-regia extractable Cd concentrations as based on soil digestion with Aqua Regia was 0.87 for the TZ soil and 0.78 for the FY soil, indicating Cd is highly reactive, which is in agreement with other studies (McBride et al, 2006;Meers et al, 2007;Römkens et al, 2009a). This ratio for Pb is about two times higher in the TZ soil (0.61) than in the FY soil (0.34).…”
Section: Physical-chemical Soil Propertiessupporting
confidence: 79%
“…Apparently, the TZ soil is heavily contaminated with Cd and Cu whereas this is the case with respect to Cd and Zn for the FY soil. The ratio between the reactive Cd concentrations as determined by soil extraction with 0.43 M HNO 3 and the aqua-regia extractable Cd concentrations as based on soil digestion with Aqua Regia was 0.87 for the TZ soil and 0.78 for the FY soil, indicating Cd is highly reactive, which is in agreement with other studies (McBride et al, 2006;Meers et al, 2007;Römkens et al, 2009a). This ratio for Pb is about two times higher in the TZ soil (0.61) than in the FY soil (0.34).…”
Section: Physical-chemical Soil Propertiessupporting
confidence: 79%
“…Apparently, Zn and also Ni in the samples from this study are mostly present in rather immobile and chemically inert fraction forms which supports observations that Zn and Ni can become immobile due to fixation and surface precipitation onto oxyhydroxides (Singhal and Gupta 1978;Bruemmer et al 1981;Elzinga and Sparks 1999;Buekers 2007). In contrast to Cr, Ni, and Zn, Cd remains highly reactive which is in agreement with data from soils for moderate climate zones (McBride et al 2006). For both HNO 3 and HCl, the median reactive to total ratio exceeds 70%, and in 5% of all soil samples, this ratio increases to more than 90%.…”
Section: Reactive Metal Poolssupporting
confidence: 76%
“…Furthermore, limited information is available on how the use of polluted irrigation water affects the distribution of metals between the total and reactive fractions in soils from paddy fields in tropical areas. For nontropical soils, metals from polluted irrigation water or sewage sludge have been demonstrated to remain in an available form decades after application (Rattan et al 2005;McBride et al 2006). Our second aim is to compare the effectiveness of the 0.43 M HNO 3 soil test, which is used widely in the European Union (EU), with tests like 0.1 M HCl or 0.05 M EDTA method used in Taiwan.…”
mentioning
confidence: 99%
“…The exception was for Cu, which was found to change once organic matter was removed, indicating Cu was predominantly associated with organic matter. By contrast, McBride et al [405] suggested that biosolids high in Fe and Al rich mineral phases was not effective in increasing Cd sorption in 20 year old biosolid amended soils. Although there is evidence to suggest long-term stability of biosolids, the importance of 'tailormade' organic amendments with other materials such as P or Fe rich materials is therefore likely to improve their environmental impact in the field.…”
Section: Efficacy Of Organic Amendments For Bioremediationmentioning
confidence: 87%